Inovasi Berbagai Media Tanam Berbasis Blotong dan Pruning pada Produktifitas Tanaman Kyuri (Cucumis Sativus L.) - Puspitorini, Palupi; Daratista, Hesti; Endrawati, Tri; Serdani, Army Dita; W, Alfan Setya; Sulistyowati, Retno; Suyani, Ida Sugeng; Umari, Iskandar; Maimunah, Maimunah; Faturrahman, Faturrahman; Amiroh, Ana (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Kyuri (Cucumis sativus L) plants have good economic value and are very much needed for health. In its cultivation, good media and pruning are needed to stimulate the growth of new productive branches which are very much needed in increasing production. This study aims to compare the filter cake planting media and pruning techniques to increase the growth and yield of kyuri cucumber plants. This study used a factorial randomized block design consisting of 2 factors, repeated three times. M1: filter cake and kettle ash (BK), M2 filter cake and rice husk charcoal (BS), M3 Soil, rice husk charcoal and manure (TSK), and M4: Soil and Cocopeat and Manure (TCK). Factor 2: Pruning System, where P1 without pruning, P2 prunes the shoots on the main stem and the shoots of three lateral branches (PP3L), and P3 prunes the shoots on the main stem and the shoots of five lateral branches (PP5L). The variables measured include plant height, stem diameter, number of leaves, number of fruits, fruit weight, and fruit length. Data analysis using analysis of variance (ANOVA) with a significance level of 5%. If the ANOVA results show a significant difference, further testing is carried out using the Duncan test with a level of 5%. The best treatment combination is M2P2, namely the use of filter cake planting media: rice husk charcoal 5: 2 and pruning the main stem and three lateral branches which can produce an average plant height of 166.2 cm, Stem Diameter 12.1 mm, Number of Leaves 22.3, Number of Fruits 7.1, Fruit Weight 337.3 kg, Fruit Length 28.4